Pengaruh Self-Esteem, Rejection Sensitivity Dan Avoidant Attachment Terhadap Fear Of Rejection Pada Remaja Akhir Dan Dewasa Awal (17-25 Tahun) - Ahmad Febrian Fauzi (Jurnal Psikologi, 2026)
Fear of rejection is a psychological experience that often emerges in late adolescence and early adulthood when individuals begin to develop more complex interpersonal relationships. Various psychological factors, such as self-evaluation, sensitivity to potential rejection, and interpersonal attachment patterns, may influence how individuals perceive and respond to the possibility of being rejected. This study aimed to examine the influence of self-esteem, rejection sensitivity, and avoidant attachment on fear of rejection among individuals aged 17–25 years. This study employed a quantitative approach with a cross-sectional design. Data were collected from 150 respondents using Likert-scale questionnaires measuring self-esteem, rejection sensitivity, avoidant attachment, and fear of rejection. The data were analyzed using multiple linear regression after meeting classical assumption tests. The results showed that self-esteem had a negative and significant effect on fear of rejection, indicating that individuals with higher self-esteem tended to experience lower fear of rejection. In contrast, rejection sensitivity and avoidant attachment had positive and significant effects on fear of rejection. Simultaneously, the three independent variables significantly predicted fear of rejection among participants. In conclusion, fear of rejection in late adolescence and early adulthood is influenced by the combined roles of self-evaluation, sensitivity to potential rejection, and interpersonal attachment patterns. These findings highlight the importance of both intrapersonal and interpersonal psychological factors in understanding individuals’ responses to perceived social rejection.